The Influence Of Remote Work On The Performance Of Remote Workers: The Mediating Role Of Work-Family Conflict And Work-Life Balance - Dinda Cornelia; Nasution Nasution (UNIVED Press, 2024)
The objective of this study is to assess the influence of remote work on the performance of employees. The present study additionally examined the intermediary function of work-family conflict and work-life balance in the relationship between remote work and performance. The present study employs a quantitative research methodology. The utilization of questionnaire instruments for data collection techniques. The research sample consisted of 230 individuals who were engaged in remote employment. The data analysis was conducted utilizing the Partial Least Squares (PLS) method. The findings of the study indicate that the implementation of remote work has a significant impact on the performance of employees. Furthermore, the impact of remote work on performance is partially and competitively mediated by work-life balance. Furthermore, it should be noted that the presence of work-family conflict does not serve as a mediator for the relationship between remote work and performance.